Children's Views on Long-Term Screening for Type 1 Diabetes. (October 2014) - Swartling, Ulrica; Helgesson, Gert; Ludvigsson, Johnny; Hansson, Mats G.; Nordgren, Anders
There are an increasing number of medical research studies involving children, including many long-term birth cohort studies. Involving children raises many issues, and little is known about children's own views. This study explored children's views ( N = 5, 851) on participation in a long-term screening study for type 1 diabetes. The results show that children 10 to 13 years of age have in general a positive attitude to pediatric research and emphasized trust in researchers. The children stressed the importance to receive information and to be involved in decisions. The children also reported feeling concerned about blood sampling and disease risk. Researchers involved in long-term pediatric research need to address these issues to promote involvement and decrease worry.